Comparison of robot‐assisted and open partial nephrectomy for completely endophytic renal tumours: a single centre experience. (1st August 2016) - Kara, Onder; Maurice, Matthew J.; Malkoc, Ercan; Ramirez, Daniel; Nelson, Ryan J.; Caputo, Peter A.; Stein, Robert J.; Kaouk, Jihad H.
Abstract : Objective: To compare outcomes between robot‐assisted partial nephrectomy (RAPN) and open PN (OPN) for completely endophytic renal tumours. Patients and Methods: We retrospectively reviewed 1 230 consecutive cases, consisting of 823 RAPNs and 407 OPNs, performed for renal mass at a single academic tertiary centre between 2011 and 2016. Of these, data on 87 RAPN and 56 OPN cases for completely endophytic renal tumours were analysed. Patient and tumour characteristics, operative, postoperative, functional, and oncological outcomes were compared between groups. Results: Apart from a higher prevalence of solitary kidney among OPN cases (RAPN, 5.7% vs OPN, 21.4%; P = 0.005), demographic characteristics were similar between the groups. There were no statistically significant differences in tumour size ( P = 0.07), tumour stage ( P = 0.3), margin status ( P = 0.48), malignant tumour subtypes ( P = 0.51), and grades ( P = 0.61) between the groups. Also, there were no statistically significant differences among the groups for warm ischaemia time ( P = 0.15), cold ischaemia time ( P = 0.28), and intraoperative ( P = 0.75) or postoperative (Clavien–Dindo Grade I–V, P = 0.08; Clavien–Dindo Grade III–V, P = 0.85) complication rates. The patients in the RAPN group had a shorter length of stay ( P < 0.001), less estimated blood loss ( P < 0.001), and lower intraoperative transfusion rates (0% vs 7.1%, P = 0.02). No local recurrences occurred during a median (interquartile range) follow‐up of 15.2 (7–27.2) and 18.1 (8.2–30.9) months in the RAPN and OPN groups, respectively. There was no difference in estimated glomerular filtration rate preservation rates between groups for the early ( P = 0.26) and latest ( P = 0.22) functional follow‐up. Conclusion: For completely endophytic renal tumours, both OPN and RAPN have excellent outcomes when performed by experienced surgeons at a high‐volume centre. For skilled robotic surgeons, RAPN is a safe and effective alternative to OPN with the advantages of shorter length of stay and less blood loss.